GENETIC SOURCES AND NEW SOURCE MATERIAL FOR BREEDING PUMPKINS IN THE LOWER VOLGA REGION - T. M. Nikulina; D. P. Kurunina; E. S. Maslennikova (Овощи России, 2018)
The results of the research work carried out during the period 2015-2017 are outlined. on the practical selection of pumpkin in the conditions of the Volgograd Transvolga. The results of studying the assortment of pumpkin varieties of domestic and foreign breeding in collection nurseries are presented. The most promising samples adapted to local soil and climatic conditions have high productivity (Sviteny, Chino, Marina di Chioggia, Silber Bell (USA), Kham (Laos), image (Spain), Local (Kazakhstan), Gribovskaya winter, Teshchenka , Zucchini Malchugan, and the quality of the fruit: (Chino, Chirimen nankin (Japan), Cachi JNTA (Argentina), Mantova Uyghur (Kazakhstan), Duchess, Vega F1, Sweetie, Pampushka, Green Warted Habbard (USA). A new hybrid material was obtained, an estimation of its productivity of consumer achestv, stability to bio- and abiotic factors. accessions selected promising superior standards major ecological and morphological and economically valuable traits. The characteristics of the best selected hybrid combinations are given in comparison with the standards. The most productive are hybrid combinations: Marina di Chioggia x Zorka, Zorka x Sweet banana, Silber Bell x Elegant, Sweet x Elegant, Local (Kirghizia) x Zorka, zucchini Mountain Anchor. The yield of these samples exceeds the standards by 13.3-92.2%. The quality of the fruit is distinguished by the hybrids: Marina di Chioggia x Zorka, Zorka x Marina di Chioggia, Pampushka x Elegant, Zorka x Sweet banana, Silber Bell x Elegant, Zaslavia x POOS6-07, Zorka x Oreshek, Altair x Elegant. The content of dry substances in the fruits of these samples is 2.0-8.8% higher than the standards.